2012
DOI: 10.1080/13621025.2012.707001
|View full text |Cite
|
Sign up to set email alerts
|

Post-nationalism re-considered: a case study of the ‘No One Is Illegal’ movement in Canada

Abstract: Studies of post-nationalism have declined considerably among citizenship scholars in recent decades, and have been largely ignored by social movement scholars in favour of more trans-national approaches. Using a case analysis of a migrant rights movement in Canada as evidence of a 'post-national ethics in practice', in this article I argue for a re-consideration of the usefulness of post-nationalism within current scholarship on precarious immigration status. Taking into account both the limitations and opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Research has examined, for example, the development of an international human rights regime and the protection of minority rights, the potential for globalisation to erode the relevance of nationalism to political organisation, and the emergence of supra- nation-state legal and political institutions (Arcarazo, 2015; Besson, 2006; Kostakopoulou, 2001; Nanz, 2006; Soysal, 1994; Tambini, 2001). Recently, however, a small body of scholarship has sought to re-focus the lens of post-national analysis onto micro-political discursive practices of contestation which seek to resist hegemonic nationalist framings of membership and rights (Abji, 2013, 2018; Tonkiss, 2019). Here post-nationalism is conceptualised as ‘actor-oriented’ and is studied empirically as micro-level practice (Tonkiss, 2019).…”
Section: Post-nationalism and Affectmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has examined, for example, the development of an international human rights regime and the protection of minority rights, the potential for globalisation to erode the relevance of nationalism to political organisation, and the emergence of supra- nation-state legal and political institutions (Arcarazo, 2015; Besson, 2006; Kostakopoulou, 2001; Nanz, 2006; Soysal, 1994; Tambini, 2001). Recently, however, a small body of scholarship has sought to re-focus the lens of post-national analysis onto micro-political discursive practices of contestation which seek to resist hegemonic nationalist framings of membership and rights (Abji, 2013, 2018; Tonkiss, 2019). Here post-nationalism is conceptualised as ‘actor-oriented’ and is studied empirically as micro-level practice (Tonkiss, 2019).…”
Section: Post-nationalism and Affectmentioning
confidence: 99%
“…I conceptualise this ‘post-national’ solidarity as that which exposes, troubles, problematises and resists the near hegemonic nationalist logics upon which political community and membership is built. While much of the empirical work on this subject has focused on macro-institutional change, recent research has demonstrated its relevance to understanding micro-level practices of discursive contestation against exclusionary logics of nationalism (see Abji, 2013; Tonkiss, 2019). This article contributes to this emerging literature, seeking specifically to examine the affective conditions which catalyse such post-national practice.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this article I am focusing on promigrant activism undertaken by existing members of the nation-state, rather than migrant-led activism, because my interest is in the post-national orientation of the existing membership of the political community. While in some instances this kind of pro-migrant activism has been shown, in its focus on citizenship acquisition above all else, to reproduce the exclusionary logics of citizenship regimes (Tyler 2010; Tyler and Marciniak 2013), individuals and organizations working to promote the rights of migrants and to contest the basis of the exclusions they face are working within spaces of contestation over what it means to be a member of a given political community (Abji 2013;Basok 2009;Nyers 2003). To what extent could they be understood as embodying the qualities of the post-national activist?…”
Section: Researching Post-nationalism As Practicementioning
confidence: 99%
“…In this article I argue that post-national activism is a key characteristic of the practice of post-nationalism. Post-nationalism as a concept captures the transformation of political community, rights and membership beyond their traditional basis in nationalism 1 (Abji 2013;Benhabib 2004;Habermas 1995;Müller 2007). I break with disciplinary orthodoxies in the field which have tended to focus predominantly on the top-down imposition of macro-level post-national legal and political frameworks to suggest that practices of micro-level contestation over rights and membership should themselves be a focus of analysis for scholars of post-nationalism.…”
Section: Introductionmentioning
confidence: 99%
“…There is scant information on the ways illegalization is experienced and resisted within the Canadian context. While valuable work has been published recently on this phenomenon (Fortier, 2013; Abji, 2013; Villegas, 2012; Goldring and Landolt, 2013), there is much to be done. This paper provides additional analysis regarding the methods employed by grassroots organizers to resist illegalization of undocumented communities and the effects on the latter.…”
Section: Introductionmentioning
confidence: 99%